Impaired Motor Function in the Affected Arm Predicts Impaired Postural Balance After Stroke: A Cross Sectional Study - Rafsten, Lena; Meirelles, Christiane; Danielsson, Anna; Sunnerhagen, Katharina S. (Frontiers in Neurology, 2019)
Background: Impaired postural balance is a common symptom after stroke and a common cause of falling. Most common daily tasks use arm and hand movements. Impairment in an upper extremity is a common stroke symptom, affecting 50–80% in the acute phase after stroke, and 40–50% in the sub-acute phase. The impact of leg function on postural balance has been investigated in several studies, but few have stressed the importance of arm function on postural balance. Objective: To explore whether there is any association between arm function and postural balance after stroke. Method: A cross sectional study where 121 adults (mean age: 70 ± 12.3 years, 72 men) from two different data sources, Gothenburg Very Early Supported Discharge (GOTVED), and a study by Carvalho et al. were merged. Time for assessments ranged from 1 to 13 years when the patients were in the chronic phase. The dependent variables were Berg Balance scale (BBS) and Time Up and Go (TUG) both dichotomized to “impaired postural balance” and “not impaired postural balance.” As independent variables, the Fugl-Meyer Assessment-Upper Extremity (FMA-UE) scale was used. The FMA-UE was presented with the total score. Results: The motor function in the arm affected after stroke onset correlated with postural balance both measured with the BBS (0.321, p < 0.001) and the TUG (−0.315, p = 0.001). Having impaired motor function in the arm was significantly associated with impaired postural balance assessed with the BBS with OR = 0.879 (CI 0.826–0.934, p < 0.001). Regression analysis with the TUG showed the same result, OR = 0.868 (CI 0.813–0.927, p < 0.001) for FM-UE. Conclusion: The motor function of the affected arm was significantly associated with impaired postural balance post stroke, as assessed by BBS or TUG. It could be of clinical importance to be aware of the fact that not only lower extremity impairment, but also arm function can have an impact on postural balance in a late stage after stroke. Trial Registration: VGFOUGSB-669501.